THE BENEFITS AND PROTECTION OF CHILDREN IN DETERMINATION OF GUARDIANSHIP (A CASE STUDY OF DETERMINATION OF THE SHARIA COURT OF BANDA ACEH NUMBER 2/PDT.P/2021/MS.BNA) - Ghifar Afghany; Ilyas Ilyas; Teuku Muttaqin Mansur (Universitas Islam Negeri Mataram, 2023)
Determination of The Sharia Court Of Banda Aceh Number 2/Pdt.P/2021/MS.Bna, which determines the biological mother as the guardian of her biological child, causes a legal conflict. On the one hand, based on the provisions of Article 47 of the Marriage Law, the biological mother, as the parent, represents the child in carrying out legal actions. On the other hand, based on this determination, the biological mother as guardian represents the child in legal actions. This research explains the method of legal discovery and legal considerations in determining guardianship. This research is normative legal research. Secondary data sources come from books, texts, journals, magazines, newspapers, documents, laws and regulations, etc. Research findings show that in the Determination Of The Sharia Court Of Banda Aceh Number 2/Pdt.P/2021/MS.Bna, the judge has carried out a legal construction of analogous arguments, namely Article 47 of the Marriage Law, which cannot resolve the case. However, the events faced in substance it is similar to other regulations related to guardianship, so when Article 47 of the Marriage Law cannot resolve the problem, this provision can be waived. An applicant who is able and has good faith in taking care of himself and the assets of the child who will be under his guardianship in the best possible way and solely for the benefit or benefit of the child, in the perspective of child protection theory, is entitled to be granted guardianship rights. In the Determination Of The Sharia Court Of Banda Aceh Number 2/Pdt.P/2021/MS.Bna there is benefit and harm, what becomes madarat is that if the petition is rejected, the child is abandoned because there is no one to take care of themselves and their property, while what becomes maslahah is if the petition is granted by appointing the Petitioner as the guardian of their children, then the objectives of the Shari’a can be fulfilled, namely take care of the soul of the child and protect the property of the child.